On Invariant Speed of Light - Orlov, S. A. (International Journal of Scientific Research in Civil Engineering, 2017)
A new physical model of the appearance of light, properties, and its trajectory. Explains the paradox of invariance and isotropy of light based on the laws of classical physics.